2017
DOI: 10.1016/j.chemosphere.2016.10.039
|View full text |Cite
|
Sign up to set email alerts
|

The attachment of colloidal particles to environmentally relevant surfaces and the effect of particle shape

Abstract: Despite the prevalence of nonspherical colloidal particles, the role of particle shape in the transport of colloids is largely understudied. This study investigates the attachment of colloidal particles onto environmentally relevant surfaces while varying particle shape and ionic strength. Using quartz crystal microbalance and atomic force microscopy measurements, the role of particle shape was elucidated and possible mechanisms discussed. The attachment of both spherical and stretched polystyrene colloidal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…A main emphasis of our work is the introduction of plant-based colloids in the stabilization of multiphase systems, particularly the emulsion’s oil/water interfaces. The associated processes and the state of dispersion are principally regulated by the nature of the colloidal particles and the conditions of the surrounding medium as well as the presence of dissolved substances . At the oil/water interface, ionic strength and pH affect the surface charge of the adsorbed particles, defining the activity and the stability of the multiphase system, which can be further tailored by steric interactions, especially in the presence of adsorbed, soft polymeric layers …”
Section: Key Adsorptive Features Of Plant-based Colloidsmentioning
confidence: 99%
“…A main emphasis of our work is the introduction of plant-based colloids in the stabilization of multiphase systems, particularly the emulsion’s oil/water interfaces. The associated processes and the state of dispersion are principally regulated by the nature of the colloidal particles and the conditions of the surrounding medium as well as the presence of dissolved substances . At the oil/water interface, ionic strength and pH affect the surface charge of the adsorbed particles, defining the activity and the stability of the multiphase system, which can be further tailored by steric interactions, especially in the presence of adsorbed, soft polymeric layers …”
Section: Key Adsorptive Features Of Plant-based Colloidsmentioning
confidence: 99%
“…Particles with different morphologies can have distinct colloidal properties and toxicity. , We thus selected three types of Al 2 O 3 particles (NPs, bulk particles (BPs), and fibers) as model minerals in the present work. The main objectives were to investigate (1) the effect of Al 2 O 3 particles with different morphologies on the toxicity of GO to freshwater algae; (2) the mechanism for the heteroaggregation-induced toxicity change; and (3) the roles of NOM and exposure sequence in GO-Al 2 O 3 heteroaggregation and related toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…15 We, and others, have been interested in the effect of bacterial shape and flexibility on rejections from membrane filters. [19][20][21] It has been demonstrated that particle size, shape, and surface properties can play a role in nanoparticle separations and in their detection and environmental fate. 14,16 The impact of particle shape on transport in porous media and in attachment to environmentally relevant surfaces has also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…14,16 The impact of particle shape on transport in porous media and in attachment to environmentally relevant surfaces has also been studied. [19][20][21] It has been demonstrated that particle size, shape, and surface properties can play a role in nanoparticle separations and in their detection and environmental fate. 22,23 The rejection coefficient is a transport parameter characterizing solute rejection from a porous membrane and is defined by considering particle flux through the membrane, N s , relative to particle flux in an unbounded fluid: 24…”
Section: Introductionmentioning
confidence: 99%